2020
DOI: 10.3390/chemengineering4020028
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Research on Contamination of Oil Well Cement with Oil-based Drilling Fluid and the Need of New and Accurate Correlations

Abstract: Drilling fluids and oil well cement are important well barriers. Their compatibility affects the long-term integrity of the well. The mixing of drilling fluid with the oil well cement causes contamination of oil well cement. If the contamination is due to diesel/oil-based drilling fluid (OBF) it adversely affects the rheological and mechanical properties of oil well cement—in other words, the long-term integrity of the well. An initial study on OBF contamination of oil well cement was carried out two decades a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Arbad et al [41] have shown the importance of measuring the bonding between casing and cement and compared these properties with other cement mechanical features such as shear strength and unconfined compressive strength. The paper highlights first a simple yet effective method to measure and compare the so-called interfacial bonding shear strength of casing-cement interaction as well as pure shear strength.…”
Section: Other Next-generation Ideas That Affect Drillingmentioning
confidence: 99%
“…Arbad et al [41] have shown the importance of measuring the bonding between casing and cement and compared these properties with other cement mechanical features such as shear strength and unconfined compressive strength. The paper highlights first a simple yet effective method to measure and compare the so-called interfacial bonding shear strength of casing-cement interaction as well as pure shear strength.…”
Section: Other Next-generation Ideas That Affect Drillingmentioning
confidence: 99%
“…These structures will reduce the liquidity of the cement slurry because the free water is tied. Skalle and Sveen (1991) and Aughenbaugh et al (2014) showed another reason for cement strength degradation. They noted that the phase of high-water activity/low-salinity cement might invert to low-water activity/high salinity because of osmotic forces.…”
Section: Introductionmentioning
confidence: 98%
“…However, some traces of drilling mud will stay in the annulus. As a result, the cement will be contaminated with drilling fluid, which leads to degradation of the cement integrity (Arbad and Teodoriu 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,49 Various factors can contribute to cement degradation during UHS, such as the presence of CO 2 in the brine/formation, 30 the generation of hydrogen sulfide, 50 and the existence of fractures in the cement sheath or microbial activities that lead to casing corrosion. 51 Therefore, addressing and understanding the associated issues of wellbore integrity during UHS are crucial for successful long-term containment/utilization of hydrogen as an energy source.…”
Section: Introductionmentioning
confidence: 99%